Good governance: a critical introduction - Malik, Maszlee (IIUM Press, 2015)
Governance is both a very new and very old subject in political science. It marks a return to the conception of political study organized around key words like constitution, government, polity, politics and other related themes. While ‘Good Governance’ agenda as introduced by Bretton Woods’ institutions according to the Washington Consensus is a result of conventional developmental theories, and represents the contemporary kernel of truth on how to develop. This small book aims to bring to the readers a general conceptual idea of Good Governance as part of Washington Consensus products and to understand critics launched against it from different point of views. This small effort is dedicated to the beginners who are trying to understand the basic idea of Good Governance from a holistic point of view and from its bigger picture.